2020
DOI: 10.1186/s12874-020-01059-y
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus disease 2019 (COVID-19): an evidence map of medical literature

Abstract: Background: Since the beginning of the COVID-19 outbreak in December 2019, a substantial body of COVID-19 medical literature has been generated. As of June 2020, gaps and longitudinal trends in the COVID-19 medical literature remain unidentified, despite potential benefits for research prioritisation and policy setting in both the COVID-19 pandemic and future large-scale public health crises. Methods: In this paper, we searched PubMed and Embase for medical literature on COVID-19 between 1 January and 24 March… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
55
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 60 publications
(50 reference statements)
3
55
0
7
Order By: Relevance
“…This finding is congruent with the high output of narrative reviews and expert opinions seen in our study, which encompasses these subtypes of publications. Additionally, Chahrour et al [ 11 ] and Liu et al [ 16 ] reported a lack of RCTs, which was also affirmed by our study. Overall, the findings of our study, and others, collectively suggest the need to increase production of high-quality research, such as RCTs, systematic reviews, and meta-analyses, to better understand COVID-19 and explore potential interventions and treatments.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This finding is congruent with the high output of narrative reviews and expert opinions seen in our study, which encompasses these subtypes of publications. Additionally, Chahrour et al [ 11 ] and Liu et al [ 16 ] reported a lack of RCTs, which was also affirmed by our study. Overall, the findings of our study, and others, collectively suggest the need to increase production of high-quality research, such as RCTs, systematic reviews, and meta-analyses, to better understand COVID-19 and explore potential interventions and treatments.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, much of the current research focuses on themes and topics discussed in published papers. Zhang and Shaw [ 15 ] and Liu et al [ 16 ] identified that a large amount of research has been focused on virology, epidemiology, and immunology. Liu et al [ 16 ] also analyzed study-type trends and found that the majority of publications were opinion pieces, editorials, and news.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike prior analyses of the scientific literature on coronaviruses, ours did not limit to records in English ( Liu et al, 2020 ; Nowakowska et al, 2020 ; Tao et al, 2020 ; Zhai et al, 2020 ) or English and Chinese only ( Yu et al, 2020 ). We additionally extracted records from more than two databases ( Haghani et al, 2020 ; Liu et al, 2020 ) and included editorials, commentaries, letters, case reports, news, and narrative reviews ( Liu et al, 2020 ; Yu et al, 2020 ). In addition to looking at the number and countries of origin of publications, we also examined indicators related to international collaboration, funding, and research quality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published bibliometric analyses either looked at research output on various scientific and medical topics of all coronavirus outbreaks including the Severe Acute Respiratory Syndrome (SARS) and the Middle East Respiratory Syndrome (MERS) ( Bonilla-Aldana et al, 2020 ; Haghani et al, 2020 ; Liu et al, 2020 ; Tao et al, 2020 ; Yu et al, 2020 ; Zhai et al, 2020 ) or were limited to the current COVID-19 pandemic overall ( De Felice and Polimeni, 2020 ; Nowakowska et al, 2020 ). Our study is unique in that it examined an underexplored area in the COVID-19 research ( Liu et al, 2020 ), namely, the trend in mental health research, and compared the findings with two prior distinct viral outbreaks.…”
Section: Discussionmentioning
confidence: 99%